The Haunting of Loch Ness Castle: Bigfoot and Nessie #2 - Campbell, Chelsea M.; Knetzger, Laura, 1990-; Penguin Random House (New York : Penguin Workshop, 2023)
While visiting Nessie's home, Loch Ness Castle, Bigfoot and Nessie encounter a ghost and Nessie stands up to her overbearing mother.
New Kids Book Winter 2024.
Ages 6-9.
Keywords: Sasquatch -- Comic books, strips, etc; Haunted places -- Comic books, strips, etc; Ghosts -- Comic books, strips, etc; Loch Ness monster -- Comic books, strips, etc; Graphic novels